Pengaruh Lokasi, Store Atmosphere, Dan Brand Image Terhadap Keputusan Pembelian Pelanggan Pada Tomoro Coffee Cabang Dinoyo - Sabila, Uchria Latifa; Basalamah, Muhammad Ridwan; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this study is to examine the influence of location, store atmosphere, and brand image on purchasing decisions among customers of Tomoro Coffee at the Dinoyo branch. The research approach employed is quantitative, with data collection conducted through a questionnaire. The population of this study consists of customers of Tomoro Coffee at the Dinoyo branch. The sample size was determined using the Maholtra formula, resulting in 80 respondents selected through purposive sampling technique. This research method includes validity tests, reliability tests, normality tests, multicollinearity tests, heteroskedasticity tests, multiple regression analysis, F-test, t-test, and determination coefficient analysis. The findings of the study indicate that both simultaneously and partially, location, store atmosphere, and brand image have a positive and significant impact on purchasing decisions. Keywords: Location, Store Atmosphere, Brand Image, Purchasing Decision, Coffee Shop